2020
DOI: 10.1007/s00392-020-01638-5
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial appendage closure in patients with chronic kidney disease: results from the German multicentre LAARGE registry

Abstract: Objectives Chronic kidney disease (CKD) is associated with an increased complication rate after cardiac interventions. Although CKD has a high prevalence among atrial fibrillation patients, the impact of CKD on periprocedural complications and the outcome after an interventional left atrial appendage closure (LAAC) is unclear. The present study, therefore, aimed to investigate whether CKD influences the procedure's effectiveness and safety. Methods LAARGE is a prospective, non-randomised registry. LAAC was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 22 publications
0
26
0
3
Order By: Relevance
“…In contrast to OACs, the effectiveness and safety of LAAC in patients with chronic renal failure regardless of severity have been reported. 173,174 However, a significant association between acute kidney disease (an absolute or a relative increase in serum creatinine of >0.3 mg/dL or ≥50% of baseline value) and higher mortality was reported, thus requiring preventive strategies, especially in patients with chronic kidney disease. 175 In the ESC and AHA/ACC/HRS guidelines, 110,176 percutaneous LAAC is classified as a Class IIb indication for stroke prevention in patients at an increased risk of stroke and with contraindications to long-term OAC therapy.…”
Section: Indicationsmentioning
confidence: 99%
“…In contrast to OACs, the effectiveness and safety of LAAC in patients with chronic renal failure regardless of severity have been reported. 173,174 However, a significant association between acute kidney disease (an absolute or a relative increase in serum creatinine of >0.3 mg/dL or ≥50% of baseline value) and higher mortality was reported, thus requiring preventive strategies, especially in patients with chronic kidney disease. 175 In the ESC and AHA/ACC/HRS guidelines, 110,176 percutaneous LAAC is classified as a Class IIb indication for stroke prevention in patients at an increased risk of stroke and with contraindications to long-term OAC therapy.…”
Section: Indicationsmentioning
confidence: 99%
“…Another large study investigating outcomes in CKD patients was published as part of the multicenter Left-Atrium-Appendage occluder Register Germany (LAARGE) (24). It was a nonrandomized prospective trial of 623 patients undergoing LAAO, including 299 patients with CKD, which reported similar implantation success and periprocedural major adverse cardiac events.…”
Section: Laao In Nonvalvular Atrial Fibrillation and Ckdmentioning
confidence: 99%
“…Left atrial appendage occlusion (LAAO) represents a nonpharmacological alternative for stroke prevention in AF patients with end-stage renal disease or on hemodialysis [44]. A recent subanalysis of the LAARGE registry revealed that LAAO was safe and associated with effective stroke prevention across all CKD stages, including stage 5 (GFR < 15 mL/min/1.73 m 2 ) [45]. The available studies aimed to compare LAAO with anticoagulant therapy showed a non-inferiority of LAAO compared to warfarin [46,47].…”
Section: Patients On Dialysismentioning
confidence: 99%